An Osteological Study on the Prevalence of Postglenoid Foramen: A Rare Emissary Foramen in Human Skull - Priya, G.; Yasodai, R. (New Advances in Medicine and Medical Science Vol. 1, 2023)
The postglenoid foramen is an emissary foramen found in the temporal bone. This foramen is rare in the human skull. This chapter aims to determine the presence of post-glenoid foramen in human skulls. The study used 100 adult dry human skulls with 200 temporal bones on each side (right and left) from the Department of Anatomy at RVS Dental College and Hospital in Coimbatore, India. Two investigators visually identified the significant foramen in the selected skulls by placing them on a flat table. To determine the patency of the foramen, a probing method was used. Out of 100 skulls (200 temporal bones), only one skull showed a unilateral post-glenoid foramen on the mandibular fossa of the left side temporal bone (2% of 200). The foramen was found backwards from the glenoid fossa of the temporal bone. It lies anterior to the external acoustic meatus in the line of fusion of the squamous and tympanic part of temporal bone. The rare occurrence of the emissary foramen may cause serious pathological condition. As a result, the current study highlights one of the rare emissary foramen, the post-glenoid foramen. The surgeons may benefit from this anatomical examination of the post-glenoid foramen while operating on temporomandibular joint and inner ear malformations in order to reduce the risk of accidental bleeding during surgery.